Association between heart rate variability and ECG changes in on-duty prehospital physicians - Maleczek, Mathias; Schebesta, Karl; Hamp, Thomas; Laussner, Balthasar; Pezawas, Thomas; Krammel, Mario; Roessler, Bernhard (Frontiers in Physiology, 2025)
Background/objectivesPrehospital emergency physicians work in physically and psychologically stressful environments. During their shifts, changes in electrocardiogram (ECG) attributable to stress have been described previously. Alterations in heart rate variability (HRV) as well as in ST-T segments have been reported. Nevertheless, the association between those two parameters still remains unclear in this setting.MethodsA retrospective analysis of data collected in a previous prospective trial was conducted. The primary objective was the association of HRV metrics with the risk of ST-T abnormalities during 5-min intervals and on a mission basis. Therefore, the root mean square of successive differences (RMSSD) and standard deviation of normal-to-normal (SDNN) intervals were analysed. Additionally, variations in HRV during different phases of a mission were investigated.ResultsData of 20 physicians was analysed. SDNN was positively associated with ST-T abnormalities both on a 5 min basis (OR: 1.04, 95%CI: 1.03-1.04) and a mission basis while RMSSD was negatively associated with ST-T abnormalities evaluated per mission (OR: 0.73, 95%CI: 0.57-0.93). pNN50 was not associated with ST-T abnormalities. During patient care and patient transport HRV was significantly lower than during alarm and en-route of a rescue mission.ConclusionNo reliable correlation between HRV values and the occurrence of ST-T segment changes during missions in prehospital emergency physicians were found. Therefore, it is questionable whether HRV alone is sufficient to detect ischemia-like changes during stressful events.